Model of Tourism Terminology Implementation in Language for Tourism Purposes University Courses - Orel Frank, Tina (JOLLT Journal of Languages and Language Teaching, 2022)
Terminology is one of the key language elements in the development of communicative competence in any language for specific purposes course. Tourism, as any other field of knowledge, predisposes certain specifics in its terminology. The aim of this paper is to establish a model for effective implementation of LTP (language for tourism purposes) in a university tourism-related language course. To reach this aim tourism terminology typology has been investigated via literature review and a study of the characteristics of tourism terminology and its teaching from both teachers’ and students’ perspectives, conducted at the University of Primorska, The results are shown in a model of LTP terminology implementation that suggests methods and activities in teaching tourism terminology which tends to be rather multidisciplinary, internationalised and (de)terminologised. The findings are not limited solely to tourism-related foreign language courses but could be adapted to any LSP university course.